Oriented Nano-Microstructure-Assisted Controllable Fabrication of Metal-Organic Framework Membranes on Nickel Foam - Sun, Yuxiu (Advanced materials (Deerfield Beach, Fla.), 2016)
© 2016 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.